How perceptual learning rewires brain connectivity: lessons from the visual system in a top-down perspective - Consorti, Alan; Sale, Alessandro (Frontiers in Neural Circuits, 2025)
Neural circuits sculpt their structure and modify the strength of their connections to effectively adapt to the external stimuli throughout life. In response to practice and experience, the brain learns to distinguish previously undetectable stimulus features recurring in the external environment. The unconscious acquisition of improved perceptual abilities falls into a form of implicit learning known as perceptual learning. Despite more than a century of multidisciplinary studies, a thorough understanding of the neural mechanisms underlying perceptual learning is still missing. Increasing evidence suggests that the learning process induces global plastic remodeling across several cortical areas, tuning neural responses to changing environmental claims by reweighting the interaction between bottom-up and top-down information. Here, we will survey classic and novel findings in the field of perceptual learning research, with a particular focus on visual perceptual learning.